Disseminated Nocardiosis: A Successful Blind Strategy of Treatment in an HIV Infected Patient - Ana C. Guerra; Dário Batista; Maria J. Aleixo; Paulo Saraiva; Maria J. Aguas (Case Reports in Infectious Diseases)
Background. Nocardiosis is a rare disease that mainly affects severely immunocompromised patients. Symptoms are nonspecific and microbiological isolation is difficult, hiding the diagnosis. Treatment should be guided by species and susceptibility testing. Findings. We report a clinical case of a disseminated nocardiosis in a patient with HIV and HVB infections. Interpretation. Diagnosis should be presumed early and microbiological conditions should be optimized, in order to identify the species and achieve antibiotic susceptibility testing. This is a very important step to choose an effective therapeutic regimen or alternative options.